Doubly disadvantaged? The relative age effect in Poland`s basketball players - Rubajczyk, K.; Swierzko, K.; Rokita, A. (Journal of Sports Science & Medicine, 2017)
The aim of this study was to identify the relative age effect (RAE) in young Polish male (n = 3849) and female (n = 3419) basketball players aged 14 to 22 years competing in the elite games of the Polish Youth Championships. The distribution of birth dates, body height, players` match statistics, and the results of teams participating in championships were identified. The RAE was observed in male and female group, regardless of players age. Nevertheless, the greatest disproportion in the distribution of dates of birth was found in U16 group of boys (V = 0.25, p < 0.0001). Significant differences in body height were identified in U14 and U16 groups of boys (p < 0.0001) and U14 group of girls (p < 0.01). The RAE was the most detrimental in the group of boys from teams ranked 9th or lower (p < 0.0001). The groups of male and female basketball players from the top 3 teams had the highest average body height (p < 0.001). In U14 boys, significantly higher match results and performance index ratings (PIR) were observed for players born in the first half of a calendar year. The research results show the impact of the RAE on the success of youth basketball teams in Poland. The month of birth, body height and sex may determine sporting achievements in youth basketball. Coaches should consider the chronological age and pubertal growth acceleration (APHV-age at peak height velocity) of players to optimize the process of identifying gifted basketball players, especially among boys of 14 years of age. Key Points: